On Some Chaotic Aspects and Center Manifold Reduction of ACT Nonlinear System - Chowdhury, A. Roy; Ray, A.; Saha, P. (Journal of Applied Nonlinear Dynamics, 2026)
Chaotic properties of a new nonlinear dynamical system, namely ACT system, are analyzed through a detailed analysis of its bifurcation diagram, attractor formation, bi-parametric Lyapunov plots. Due to the presence of many parameters in the system it shows a very rich structure in all respects. Details of stability analysis and its relation to the corresponding center manifold reduction are also studied.